1995
DOI: 10.1143/jjap.34.2745
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Mechanism of a Scientific Toy “Girigiri-Garigari”

Abstract: “Girigiri-Garigari” is the Japanese name of a scientific toy which consists of a square rod and a propeller. The wooden rod has several notches along its long edge, and the propeller is loosely attached to one end of the rod by a nail. The propeller is rotated by rubbing the rod with another bar. A player can control the revolution direction of the propeller in two ways, by changing the gripping position or condition of the rod. This paper presents an experimental study on the mechanism of this toy. Main resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
5
1
Order By: Relevance
“…Within this paper, we have performed an extensive research of the device, aiming to pinpoint the essential phenomenon that causes the propeller to rotate. Contrary to the hypotheses presented in the previous works on this topic, in particular, works by Wilson 4 and Satonobu 3 , we have shown that an elliptical movement of the stick is not necessary to induce a rotational movement of the propeller – on the contrary, a purely linear motion of the stick induces the highest speeds of the propeller. We have also shown that contrary to ideas presented so far 4 , 5 , there is no synchronization effect between the motion of the stick and the propeller – by purely harmonic motion of the stick, the propeller was able to accelerate from rest to high frequencies (however not reaching the driving frequency), and the stabilized speed of the propeller was strongly dependent on the amplitude of the oscillations.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Within this paper, we have performed an extensive research of the device, aiming to pinpoint the essential phenomenon that causes the propeller to rotate. Contrary to the hypotheses presented in the previous works on this topic, in particular, works by Wilson 4 and Satonobu 3 , we have shown that an elliptical movement of the stick is not necessary to induce a rotational movement of the propeller – on the contrary, a purely linear motion of the stick induces the highest speeds of the propeller. We have also shown that contrary to ideas presented so far 4 , 5 , there is no synchronization effect between the motion of the stick and the propeller – by purely harmonic motion of the stick, the propeller was able to accelerate from rest to high frequencies (however not reaching the driving frequency), and the stabilized speed of the propeller was strongly dependent on the amplitude of the oscillations.…”
Section: Discussioncontrasting
confidence: 99%
“…( 2) , the readings of the position of the nail are presented for two cases – one is elliptical, resulting from positioning the stick on the side of the subwoofer, and one straight and nearly vertical, when the stick is placed in the center. This shows that with our experimental device, we were able to mimic the outcomes produced in the close-to-original gee-haw whammy diddle in refs 3 , 4 . For elliptical movement, we confirmed the results obtained so far – the direction of the rotation of the propeller was predefined by the direction of the elliptical movement (areal velocity).…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…Girigiri-Garigari is a toy with a propeller that rotates through vibration [5]. It grew in popularity at the Acoustical Society of Japan's events, and it remains one of the most popular exhibits because participants can take the toy home after they make it (Fig.…”
Section: Handicrafts Of Girigiri-garigarimentioning
confidence: 99%